Complete plastid genome of an alpine plant Gentiana filistyla (Gentianaceae) and phylogenetic analysis - Hui-Yuan Ya; Rui-Qi Zhou; Bei-Bei Li; Peng-Cheng Fu (Mitochondrial DNA. Part B. Resources, 2020)
The complete plastid genome of Gentiana filistyla, occurring in Hengduan Mountains with high altitudes, was determined and analyzed in this work. It had a circular-mapping molecular with the length of 139,476 bp, has similar gene composition with G. section Kudoa but contains eight less ndh genes than the available species from sections Cruciata, Microsperma and Frigidae. Phylogenetic analysis showed that G. filistyla clustered together with section Kudoa rather than sections Microsperma and Frigidae. The plastome provided in this work would be useful for elucidation of phylogenetics and evolution in Gentiana.